Free Medial Plantar Flap Versus Free Dorsal Myocutaneous Flap for the Reconstruction of Traumatic Foot Sole Defects. (May 2020) - Han, Yan; Han, Yudi; Song, Baoqiang; Guo, Lingli; Tao, Ran; Chai, Mi
Abstract : Background: Trauma can cause large defects in the weight-bearing foot sole. The reconstruction of such defects poses a major challenge in providing a flap that is durable, sensate, and stable. The pedicled medial plantar flap has been commonly used for reconstructing heel and plantar forefoot defects; however, the ipsilateral instep region is usually compromised by trauma. The purpose of this article was to report the use of contralateral free medial plantar flaps for the coverage of weight-bearing plantar defects and to compare these with distant free flaps. Methods: Between 2005 and 2019, 15 patients (10 men and 5 women) with weight-bearing foot plantar defects were treated with a contralateral medial plantar flap, 11 (7 men and 4 women) with either a latissimus dorsi flap or a scapular flap. The average age was 18.07 ± 10.14 years (range, 4–34 years) and 26.55 ± 13.05 years (range, 13–56 years), respectively. Surgery was performed as a primary or secondary reconstruction after a trauma by the same surgical team. Results: The mean size of defects was 9.73 ± 3.55 × 6.43 ± 2.8 cm in the contralateral free medial plantar flap group and 17.14 ± 6.84 × 11.41 ± 4.29 cm in the free dorsal flap group. All flaps survived in both groups. In the instep flap group, the appearance was satisfactory, the flap was durable, and tactile sensation was preserved in all patients, and none required a revision procedure. Two patients experienced delayed union of the donor-site grafted skin. In the dorsal flap group, 5 patients complained of a partial necrosis or delayed union at the recipient site, and 9 developed recurrent ulcerations over the weight-\bearing area. Five patients achieved only partial sensation in the flap. Conclusions: The contralateral medial plantar flap provides superior appearance, duration, and sensation over distant muscle flaps, without recurrent ulcerations. However, dorsal myocutaneous flaps may be used as a substitute when the defects are beyond the maximum boundaries of the instep area or are combined with bone loss.